Core–Shelled Low‐Oxidation State Oxides@Reduced Graphene Oxides Cubes via Pressurized Reduction for Highly Stable Lithium Ion Storage. (29th February 2016) - Zhang, Kan; Li, Ping; Ma, Ming; Park, Jong Hyeok
Abstract : Metal oxides have been regarded as promising next‐generation anode materials for rechargeable lithium ion batteries; however, their poor stability, which is caused by large volume changes during repeated lithiation/delithiation, remains a challenge. Here, conformally encapsulated low‐oxidation state oxide cubes with reduced graphene oxide (RGO) obtained via a new pressurized reduction consisting of external mechanical compression and internal thermokinetic reduction from highly porous metal oxides/RGO aerogel (RGOA) are reported. Using single crystalline (SC) cobalt oxides and iron oxide cubes as model systems, the SC‐Co3 O4 or Fe2 O3 cube/RGOA are pressurized into compacted xerogel along with a uniform thermokinetic reduction, which result in topotactic transformation to core‐shelled CoO/RGO or Fe3 O4 @RGO cubes. The SC‐CoO and SC‐Fe3 O4 cubes isolated perfectly in the RGO shells have dramatically improved their cycling stabilities for lithium ion storage to hundreds of times. Abstract : The lithium‐ion storage stability of the core/shelled low‐oxidation state oxide/RGO cubes can be prolonged by at least 400 times.